The Psychological Needs of the Spouses During the COVID-19 Coronavirus Epidemic on the Basis of the Testimonies of Members of the Home Church Community - Opalach, Cezary Wojciech (Studia Warmińskie, 2021)
: This study aimed to verify the hypothesis that the situation of the COVID-19 coronavirus epidemic had a negative impact on the fulfillment of the psychological needs of spouses, belonging to the Home Church community in terms of A. Maslow’s theory of needs. The analysis of 37 reports of spouses belonging to the aforementioned community did not confirm this hypothesis, as it was found that out of 254 references to needs, only 82 mentioned their deprivation and 172 concerned their satisfaction. It appears that the sources of such results are threefold. The first seems to be the lack of strong and stable social structures. The low level of functioning of these structures, according to the concept of A. Maslow, negatively correlates with a sense of security that means it is responsible for a low level of realization of psychological needs. The second source might be the life philosophy of the examined couples, focusing on spiritual and family development. Since these elements constitute the essence of the formation of the Home Church community it can be concluded that belonging to this community positively affects the sense of security and the fulfillment of psychological needs. The third source might be the level of religiosity of the examined couples, which positively correlates with the fulfillment of psychological needs of the spouses, although in our analysis this variable was not controlled. Only further studies will determine which of the two last reasons and to what extent decides about the final shape of the obtained results.